2017
DOI: 10.1530/eje-17-0372
|View full text |Cite
|
Sign up to set email alerts
|

Optimal follow-up strategies for adrenal incidentalomas: reappraisal of the 2016 ESE-ENSAT guidelines in real clinical practice

Abstract: We advocate that no follow-up imaging is required if the detected adrenal mass is <4 cm and has clear benign features. However, prospective studies with longer follow-up are needed to confirm the appropriate follow-up strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 31 publications
(50 reference statements)
1
38
0
1
Order By: Relevance
“… 2 7 However, the best cutoff value for mass size in the COAR cohort for predicting ACC was 3.25 cm and was lower than that in the SIE cohort. 8 Although the reason is currently uncertain, except for the advance in CT technology detecting smaller AIs, a recent retrospective study investigating Korean AIs also suggested an optimal cutoff value for mass size as 3.4 cm for differentiating malignant from benign lesions, 40 similar with the cutoff value in the COAR cohort. Given the high mortality rate associated with ACCs, we suggest excision of lesions ≥3 cm.…”
Section: Discussionmentioning
confidence: 90%
“… 2 7 However, the best cutoff value for mass size in the COAR cohort for predicting ACC was 3.25 cm and was lower than that in the SIE cohort. 8 Although the reason is currently uncertain, except for the advance in CT technology detecting smaller AIs, a recent retrospective study investigating Korean AIs also suggested an optimal cutoff value for mass size as 3.4 cm for differentiating malignant from benign lesions, 40 similar with the cutoff value in the COAR cohort. Given the high mortality rate associated with ACCs, we suggest excision of lesions ≥3 cm.…”
Section: Discussionmentioning
confidence: 90%
“…The reported frequency of ACC is derived from highly selected patient populations and may not reflect the prevalence rates observed in population-based studies. Combining the studies reported from 1982 to 2008, the ACC etiology of adrenal incidentaloma ranged from 0 to 14% (3,4,5,6,7). Further, studies including patients…”
Section: Introductionmentioning
confidence: 99%
“…The best known causes of bilateral adrenal masses are related to macronodular adrenal hyperplasia, potentially regulated by aberrant G proteincoupled receptors (21), familial pheochromocytoma, primary hyperaldosteronism (22), ARMC5 gene mutation (23,24), 21-hydroxylase deficiency, multiple endocrine neoplasia type 1 (MEN-1), infectious diseases, nonfunctioning tumor or metastatic diseases (18). However, a direct relationship between adrenal incidentalomas and altered GR signaling has never been investigated thus far nor evoked in recent published guidelines (25,26).…”
Section: Introductionmentioning
confidence: 99%